PLASMA IRISIN AND HEAT SHOCK PROTEIN 70 LEVELS IN PRIMARY RAYNAUD'S PHENOMENON AND SYSTEMIC SCLEROSIS - Gozel, Nevzat; Karatas, Ahmet; Yardim, Meltem; Kinaci, Mesude Seda; Ulu, Ramazan; Demircan, Fatih; Koca, Suleyman Serdar (Parlar Scientific Publications (P S P), 2018)
The pathogenesis of Raynaud's phenomenon (RP) is not fully elucidated, yet. The aim of the present study was to evaluate plasma irisin and heat shock protein (HSP) 70 levels in both primary RP and secondary RP associated with systemic sclerosis (SSc). 15 patients with primary RP, 30 patients with RP secondary to SSc, and 30 healthy controls (HC) were included in the study. Raynaud Condition Score (RCS) were performed in the primary RP and SSc groups. Modified Rodnan skin severity score (MRSS) was determined for the SSc patients. Plasma irisin and HSP 70 levels were analyzed by ELISA method. When compared to the HC group, plasma irisin and HSP 70 levels were lower in the secondary RP group, but not in the primary RP group. Plasma irisin and HSP 70 levels were not directly related with RCS in the both primary and secondary RP groups. Moreover, they were not correlated with MRSS in the secondary RP group. The results of present study can suggest that irisin and HSP 70 levels are not associated with primary RP. Its level was lower in the secondary RP (SSc) patients. Therefore, it can be concluded that decreased irisin and HSP 70 levels are related with SSc instead of RP.
Keywords: Raynaud's phenomenon; systemic sclerosis; irisin; heat shock protein 70